Dokumentasi dan Analisis Nilai Pendidikan Karakter dalam Folklor Asal Usul Desa Patia, Kabupaten Pandeglang - Al Gadri, Henri Henriyan; Trisnawati, Trisnawati (Universitas Mathla'ul Anwar Banten, 2021)
This study aims to document the folklore “The Origin of Patia Village”, Pandeglang Regency, as well as analyze the value of character education in the folklore. This study uses a qualitative method with a folklore approach. There are four stages passed in this research. The four stages are first, on-site pre-research stage, second stage of on-site research, third way of making folklore manuscripts for archiving and fourth analysis of the value of folklore character education. The results of this study are the documentation of the folklore